Anastomotic Technique and Preoperative Imaging in Microsurgical Lower-Extremity Reconstruction: A Single-Surgeon Experience. Issue 4 (April 2020) - Carney, Martin J.; Samra, Fares; Momeni, Arash; Bauder, Andrew R.; Weissler, Jason M.; Kovach, Stephen J.
Abstract : Background: The need for preoperative imaging as well as anastomotic technique (ie, end-to-side [ETS] vs end-to-end [ETE]) are areas of controversy in microsurgical lower-extremity reconstruction. The objective of this study was to (1) investigate whether preoperative imaging is mandatory and (2) to elicit if the type of anastomosis impacts clinical outcomes. Methods: A retrospective review of all patients who underwent microvascular lower-extremity reconstruction between 2007 and 2015 by a single surgeon was performed. Patients were categorized into groups based on anastomotic technique, that is, ETE versus ETS anastomosis. Patients in the ETE group were further subclassified into those who had preoperative imaging (computed tomography angiography [CTA]+) versus those who did not (CTA−). Parameters of interest included flap type, thrombosis rate, flap loss, length of stay (LOS), return to ambulation, and rate of secondary amputation. Two-sided statistical analysis was performed using Kruskal-Wallis rank-sum test and Fisher exact test. Results: One hundred twenty-eight patients were analyzed: ETE (n = 40) and ETS (n = 88). Mean follow-up for both groups was 20 ± 19 months. Anterolateral thigh flaps were most commonly performed (71%). Overall flap loss rate was 3.1% without any significant differences noted with respect to thrombosis (arterial, P = 0.09; venous, P = 0.56), flap loss ( P = 0.33), LOS ( P = 0.28), amputation ( P = 1.00), or return to ambulation ( P = 0.77). Furthermore, the availability of preoperative imaging (CTA+: N = 11 vs CTA−: N = 29) did not impact rates of thrombosis (arterial, P = 0.29; venous, P = 0.31), flap loss ( P = 1.00), LOS ( P = 0.26), or return to mobility ( P = 0.62). Conclusions: In light of similar reconstructive outcomes, we prefer to preserve distal extremity perfusion via ETS anastomoses whenever possible. Furthermore, preoperative vascular imaging angiography might not be necessary in patients with palpable pedal pulses on preoperative examination. An actionable algorithm for determining ETS versus ETE anastomosis in lower-extremity reconstruction is presented.